The Effects of Resveratrol-Rich Extracts of Vitis vinifera Pruning Waste on HeLa, MCF-7 and MRC-5 Cells: Apoptosis, Autophagia and Necrosis Interplay - Aleksandra Jovanović Galović; Nataša Jovanović Lješković; Senka Vidović; Jelena Vladić; Nikola Jojić; Milan Ilić; Tatjana Srdić Rajić; Vesna Kojić; Dimitar Jakimov (Pharmaceutics, 2022)
Resveratrol is a well-studied plant-derived molecule in cancer biology, with a plethora of documented in vitro effects. However, its low bioavailability and toxicity risk hamper its wider use. In this study, vine shoots after pruning were used as a source of resveratrol (RSV). The activity of subcritical water extract (SWE) and dry extract (DE) is examined on three cell lines: HeLa, MCF-7 and MRC-5. The cytotoxic effect is assessed by the MTT test and EB/AO staining, levels of apoptosis are determined by Annexin V assay, autophagia by ULK-1 expression using Western blot and NF-kB activation by p65 ELISA. Our results show that both resveratrol-rich extracts (DE, SWE) have a preferential cytotoxic effect on malignant cell lines (HeLa, MCF-7), and low cytotoxicity on non-malignant cells in culture (MRC-5). Further experiments indicate that the investigated malignant cells undergo different cell death pathways. MCF-7 cells died preferentially by apoptosis, while the HeLa cells died most likely by necrosis (possibly ferroptosis). Protective autophagia is diminished upon treatment with DE in both HeLa and MCF-7 cells, while SWE does not influence the level of autophagia. The extracts are effective even at low concentrations (below IC50) in the activation of NF-kB (p65 translocation).